2021
DOI: 10.3390/v13081657
|View full text |Cite
|
Sign up to set email alerts
|

Equine Influenza Virus and Vaccines

Abstract: Equine influenza virus (EIV) is a constantly evolving viral pathogen that is responsible for yearly outbreaks of respiratory disease in horses termed equine influenza (EI). There is currently no evidence of circulation of the original H7N7 strain of EIV worldwide; however, the EIV H3N8 strain, which was first isolated in the early 1960s, remains a major threat to most of the world’s horse populations. It can also infect dogs. The ability of EIV to constantly accumulate mutations in its antibody-binding sites e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(50 citation statements)
references
References 237 publications
1
48
0
1
Order By: Relevance
“…We live in a time of intensive development of the horse industry and transport globalization, and the risk of new outbreaks is increasing. Available EIV vaccines are effective (27), and observed differences in clinical signs and epidemic size in this study confirmed the importance of EI vaccination. Vaccine protection is adequate despite the unpredictable EIV evolution, given that vaccinal strains are regularly updated (26).…”
Section: Discussionsupporting
confidence: 79%
“…We live in a time of intensive development of the horse industry and transport globalization, and the risk of new outbreaks is increasing. Available EIV vaccines are effective (27), and observed differences in clinical signs and epidemic size in this study confirmed the importance of EI vaccination. Vaccine protection is adequate despite the unpredictable EIV evolution, given that vaccinal strains are regularly updated (26).…”
Section: Discussionsupporting
confidence: 79%
“…Requires multiple administrations to obtain a protective immune response and mainly invokes a humoral immune response [168]. Adjuvant added to improve immunogenicity [169] Subunit Yes Produced using embryonated eggs.…”
Section: Yesmentioning
confidence: 99%
“…However, it is unclear whether the extinction of the H7N7 subtype in horses is a result of vaccination campaigns, since the last isolation was in 1979 and the first vaccination trials were in 1983 [188]. Interestingly, antigenic drift of equine IAV seems to be lower than for other IAVs, delaying need for an adaptation of the vaccine strains by several years [189]. In contrast, swine IAV are faster evolving and it is challenging to adapt vaccines accordingly.…”
Section: Discussionmentioning
confidence: 99%